KAB-Newsletter-Issue-4-2023 - Sempungu, Godfrey J. (2023)
We are glad to be bringing to you the fourth Issue of the KAB Newsletter. This is another great collection of the news around the University. We are glad that this newsletter is telling the story of Kabale University’s transformation each day. I am grateful to the editorial team of contributors and editors that have made it possible to have all the key activities around the university to be documented for our stakeholders. It is our goal and resolve to make each issue better than the previous.